A Review on Optimizing Clustering Technique for Data Stream using Genetic Algorithm - Sharma, Neha; Makhija, Pawan (International Journal of Computer Sciences and Engineering, 2025)
In the current world , various sources like sensors, social media, web logs, network monitoring devices, traffic monitoring devices are generating lots of data. This huge data is arriving continuously, with high speed and changing its nature with time. Extracting useful information from the data stream demands enhancement in existing technologies of Data Mining. Clustering is an important part of data mining in which similar data points are merge into one group. Use of genetic algorithm in clustering data stream is an emerging technology. In this paper, we are discussing clustering techniques for data stream using Genetic Algorithm.